Editorial Futures Reframed, Issue 1: Darkness Reframed - van Voorst, Roanne; Cramer, Tessa (Futures Reframed, 2026)
As the climate unravels, so do our certainties. Across the world, people struggle - often in isolation, sometimes in communal gatherings - to find ways of mourning what is disappearing: melting glaciers, vanishing islands, dying coral reefs. These practices obviously do not solve the crisis but they do grow our capacity to perceive it. This inaugural issue of Futures Reframed begins there. We ask what it means to think about futures from within uncertainty, grief, and loss. In a discipline that more often associates ‘the future’ with optimism, control, and planning than with mourning and unknowing, we insist on starting from the latter. This commitment to amplifying such marginalised futures is one of the commitments that defines the Futures Reframed journal.